Effect of Environmental Stressors on the Distribution and Abundance of Macroinvertebrates in Upper Awash River at Chilimo Forest, West Shewa, Ethiopia - Dabessa, Misgana; Lakew, Aschalew; Devi, Prabha; Teressa, Hirpasa (International Journal of Zoology, 2021)
Ethiopia is experiencing deterioration in river quality resulting in adverse effects on human health and hydrobionts. This study aimed to analyse the effects of specific environmental stressors on the distribution and abundance of macroinvertebrates in the Upper Awash River. The study was conducted from January 2018 to March 2018. Macroinvertebrates were collected from five sites using standard handheld nets. Physicochemical parameters including electrical conductivity, dissolved oxygen, total phosphorous, nitrate-nitrogen, pH, dissolved oxygen and water temperature that can affect the distribution and abundance of macroinvertebrates were assessed. A total of 14,465 individuals belonging to 33 families of insects and 5 families of the noninsect group were identified. Among all recorded taxa, Diptera was the most abundant and diversified order. Macroinvertebrates among the five sites showed variation in species evenness, richness, and Shannon Diversity Index. Values obtained from biotic indices and environmental parameters indicated the presence of organic pollution at different levels. The impacted downstream site paper mill waste (Walgata) had the relatively highest H-FBI index followed by Osole (more agricultural activities) indicating that Walgata and Osole were poorer in benthic faunal diversity than other sites. In addition, as habitat and water quality degradation increased, the number and percentage of Plecoptera, Ephemeroptera, and Trichoptera (EPT) decreased. The selected metrics will be also useful for the monitoring and assessment of the riverine systems and to access the impact of different stressors. As perturbation increased, species diversity, ETHbios index, Average Score Per Taxon, and family richness decreased, while the percentage of Chironomidae, Diptera, Dominant Taxa, and Hilsenhoff Family-Level Biotic Index increased indicating that tolerant species become abundant in degraded river bodies. Environmental protection agencies of governmental and nongovernmental organizations should make awareness for the local people so that they reduce activities that affect the river. Paper factory should also monitor its effluent from directly discharging into the Upper Awash River.